Dynamic stability in the anterior cruciate ligament deficient knee - Rudolph, Katherine S.; Axe, Michael J.; Buchanan, Thomas S.; Scholz, John P.; Snyder‐Mackler, Lynn (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2001)
Some individuals can stabilize their knees following anterior cruciate ligament rupture even during activities involving cutting and pivoting (copers), others have instability with daily activities (non‐copers). Movement and muscle activation patterns of 11 copers, ten non‐copers and ten uninjured subjects were studied during walking and jogging. Results indicate that distinct gait adaptations appeared primarily in the non‐copers. Copers used joint ranges of motion, moments and muscle activation patterns similar to uninjured subjects. Non‐copers reduced their knee motion, and external knee flexion moments that correlated well with quadriceps strength. Non‐copers also achieved peak hamstring activity later in the weight acceptance phase and used a strategy involving more generalized co‐contraction. Both copers and non‐copers had high levels of quadriceps femoris muscle activity. The reduced knee moment in the involved limbs of the non‐copers did not represent “quadriceps avoidance” but rather represented a strategy of general co‐contraction with a greater relative contribution from the hamstring muscles.